Analisis Peningkatan Omset Kur Syariah terhadap UMKM Studi Kasus Pegadaian Cabang Terandam - Yuhda Suhada Franata; Joan Marta (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to examine three main things: (1) the influence of customer characteristics on the increase in MSME turnover, (2) the impact of business characteristics on the growth of MSME turnover, and (3) the extent to which credit characteristics affect the increase in MSME turnover. The data used is cross section and was obtained from PT Pegadaian Terandam Branch in 2023. The analysis method applied in this study is logistic regression. The findings show that two factors of customer characteristics, namely gender and education level, have a significant effect on increasing the turnover of MSMEs in the branch. On the other hand, the variables of age, type of business, ownership of the business premises, length of business operation, and loan amount did not show a significant influence. These findings underscore the importance of increasing the capacity of MSME actors through education, both formal and non-formal, to support business management skills and encourage turnover growth.